Quand l’auteur se livre : du vécu à la création littéraire Notes d’une musique ancienne de Salah Benlabed - Lina Bendjelloul (Revue des Sciences Humaines, 2017)
This present article is a modest work presentation and synthesis of theoretical concepts related to the issue of identity generic text. The work on which was our Master thesis was full of clues and fictional references that have enabled us to establish a double interpretation, it is therefore in the border between autobiography autofiction . The above article includes all the definitions established by theorists who were interested in this generic. By summoning and highlighting illustrations from our corpus , we were able to identify the characteristics of autobiography and self-fiction , to apply them to our corpus. The latter, analyzed and commented , gave us the image of a very rich and interesting work , given its generic dual membership ; This broadens its outlook reading and highlights its originality.